Indolic uremic solutes increase tissue factor production in endothelial cells by the aryl hydrocarbon receptor pathway - Gondouin, Bertrand; Cerini, Claire; Dou, Laetitia; Sallée, Marion; Duval-Sabatier, Ariane; Pletinck, Anneleen; Calaf, Raymond; Lacroix, Romaric; Jourde-Chiche, Noémie; Poitevin, Stéphane; Arnaud, Laurent; Vanholder, Raymond; et al. (Kidney international, 2013)
In chronic kidney disease (CKD), uremic solutes accumulate in blood and tissues. These compounds probably contribute to the marked increase in cardiovascular risk during the progression of CKD. The uremic solutes indoxyl sulfate and indole-3-acetic acid (IAA) are particularly deleterious for endothelial cells. Here we performed microarray and comparative PCR analyses to identify genes in endothelial cells targeted by these two uremic solutes. We found an increase in endothelial expression of tissue factor in response to indoxyl sulfate and IAA and upregulation of eight genes regulated by the transcription factor aryl hydrocarbon receptor (AHR). The suggestion by microarray analysis of an involvement of AHR in tissue factor production was confirmed by siRNA inhibition and the indirect AHR inhibitor geldanamycin. These observations were extended to peripheral blood mononuclear cells. Tissue factor expression and activity were also increased by AHR agonist dioxin. Finally, we measured circulating tissue factor concentration and activity in healthy control subjects and in patients with CKD (stages 3–5d), and found that each was elevated in patients with CKD. Circulating tissue factor levels were positively correlated with plasma indoxyl sulfate and IAA. Thus, indolic uremic solutes increase tissue factor production in endothelial and peripheral blood mononuclear cells by AHR activation, evoking a ‘dioxin-like’ effect. This newly described mechanism of uremic solute toxicity may help understand the high cardiovascular risk of CKD patients.